2020
DOI: 10.1111/cge.13769
|View full text |Cite
|
Sign up to set email alerts
|

GREB1L variants in familial and sporadic hereditary urogenital adysplasia and Mayer‐Rokitansky‐Kuster‐Hauser syndrome

Abstract: We would like to thank the families for their participation to this study and the members of both the MAIA (http://www.maia-asso.org) and Syndrome de Rokitansky-MRKH (http://asso.orpha.net/MRKH) associations for their contribution. We are also indebted to the physicians involved in the French national PRAM network (Programme de Recherches sur les Aplasies Müllériennes), the GACUA and the GARD research programs. We thank the GIGA Genomics Platform for technical assistance with NGS data generation. This research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 29 publications
4
41
0
1
Order By: Relevance
“…The study reported a co-segregating missense variant in GREB1L (Table 1) [24], a gene identified in 2017 to cause bilateral renal agenesis in fetuses of which several female fetuses also had uterus agenesis [73,74]. Just recently, Jacquinet et al reported four additional multiplex families with either type II MRKH syndrome or uterovaginal aplasia (fetuses) associated with renal malformations (agenesis in particular) in which pathogenic GREB1L variants were identified from WES data [72]. GREB1L now seems to be the first gene to show a strong association with type II MRKH syndrome with kidney anomalies following autosomal dominant inheritance with incomplete penetrance.…”
Section: Embryology Etiology and Geneticsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study reported a co-segregating missense variant in GREB1L (Table 1) [24], a gene identified in 2017 to cause bilateral renal agenesis in fetuses of which several female fetuses also had uterus agenesis [73,74]. Just recently, Jacquinet et al reported four additional multiplex families with either type II MRKH syndrome or uterovaginal aplasia (fetuses) associated with renal malformations (agenesis in particular) in which pathogenic GREB1L variants were identified from WES data [72]. GREB1L now seems to be the first gene to show a strong association with type II MRKH syndrome with kidney anomalies following autosomal dominant inheritance with incomplete penetrance.…”
Section: Embryology Etiology and Geneticsmentioning
confidence: 99%
“… Type I [ 55 , 56 ] c.665G > A; p.Arg222His c.722G > A; p.Arg241His c.974G > A; p.Arg325His c.1029C > A; p.Cys343* 18q11.1–2 GREB1L c.705G > T; p.Trp235Cys Additional GREB1L variants of unknown significance have been reported in unrelated MRKH syndrome patients [ 72 ]. Several GREB1L variants have been reported in female fetuses with BRA and uterus/uterovaginal agenesis [ 72 74 ]. Greb1l- null mice also have BRA and Müllerian aplasia [ 73 , 74 ].…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations